Antibodies to Neospora caninum in sheep from slaughterhouses in the state of Sao Paulo, Brazil - Paiz, Lais Moraes; Silva, Rodrigo Costa da; Menozzi, Benedito Donizete [UNESP]; Langoni, Helio [UNESP] (Brazilian Coll Veterinary Parasitology, 2015)
Neosporosis is an emergent disease responsible for considerable economic impact due to reproductive losses. Its zoonotic potential remains unknown. This study involved a survey of antibodies to Neospora caninum in slaughtered sheep and their association with epidemiological variables. Serum samples from 596 sheep from the states of Sao Paulo and Rio Grande do Sul, Brazil, were collected in two slaughterhouses located in Sao Paulo and evaluated by indirect fluorescence antibody test (IFAT), using cut-off titers of 25. Among these samples, 353/596 (59.23%; 95%CI 55.23-63.10) were positive and 263/353 (74.50%; 95%CI 69.71-78.77%) were from Rio Grande do Sul. Statistical associations were determined in the univariate analysis between the serological results and sex, breed and municipality of origin. Sheep that came from extensive breeding system showed higher chance (OR=2.09) of presenting antibodies to N. caninum in relation to those from semi-intensive system. Higher chance was also observed for the different studied breeds, except Bergamacia, in relation to Hampshire Down. The results revealed the presence of infection by N. caninum in sheep from slaughterhouses.

A neosporose é uma doença emergente responsável por considerável impacto econômico devido a perdas reprodutivas e seu potencial zoonótico permanece desconhecido. Este estudo envolveu a pesquisa de anticorpos para Neospora caninum em ovinos abatidos e sua associação com variáveis epidemiológicas. Amostras de soro sanguíneo de 596 ovinos, procedentes dos estados de São Paulo e Rio Grande do Sul, Brasil, foram colhidas em dois abatedouros localizados em São Paulo, e avaliadas pelo teste de reação de imunofluorescência indireta (RIFI), utilizando-se como ponto de corte o título de 25. Dentre essas amostras, 353/596 (59,23%; IC95% 55,23-63,10) foram positivas e dentre os ovinos positivos 263/353 (74,50%; IC95% 69,71-78,77%) eram procedentes do Rio Grande do Sul. Associações estatísticas foram determinadas na análise univariada entre os resultados sorológicos e o sexo, raça e município de origem. Ovinos oriundos de sistema de criação extensivo demonstraram maior chance (OR=2.09) de apresentarem anticorpos para N. caninum em relação aos de sistema semi-intensivo. Uma maior chance também foi observada para as diferentes raças estudadas, exceto Bergamácia, em relação à raça Hampshire Down. Os resultados revelaram a presença de infecção por N. caninum em ovinos de abatedouros.
Anticorpos para Neospora caninum em ovinos de abatedouros do estado de São Paulo, Brasil
Keywords: Neospora caninum; Serology; Sheep; Slaughterhouses; Neospora caninum; Sorologia; Ovinos; Abatedouros